Peningkatan Kelincahan Melalui Permainan Lari Bolak Balik Siswa Sdn 1 Lalebbata Kota Palopo Kelas VA - Muh Fikri Hidayatullah; Irsan Kahar; Hajeni Hajeni; Rachmat Hidayat (Universitas Hamzanwadi, 2026)
The issue of low agility among fifth-grade students at SDN 1 Lalebbata in Palopo City served as the background for this study. Based on initial observations, only 38.46% of students fell into the agile and very agile categories, while the majority struggled with changes in direction, body balance, and responding to commands. This study aims to improve students’ agility through the implementation of shuttle runs in physical education lessons. The method used was the Classroom Action Research (CAR) model by Kemmis and McTaggart, conducted in two cycles, each consisting of planning, action, observation, and reflection. The study subjects consisted of 26 students. The instrument used was an agility observation sheet with five indicators: speed, change of direction, balance, response to cues, and completion of the game. Data were analyzed using quantitative descriptive analysis of percentages. The results showed a significant improvement, from 38.46% at the initial stage to 53.84% in Cycle I, and reaching 80.77% in Cycle II, exceeding the success indicator of 75%. In conclusion, the implementation of the back-and-forth running game was effective in improving the agility of Grade 5A students.